Bioecological Classification of Juniper Plants and the Importance of Groups (Texas Journal of Agriculture and Biological Sciences, 2022)
The spruce family has been a very important plant since the dawn of time. Air purification properties of spruce plants, high level of phytonciticity, erosion in mountainous and foothill areas, wood yielding, long life, low water evaporation, high retention of dust in the air and of course, the fact that both the production of oxygen and the aesthetic pleasure of humans at the same time testify to the importance of spruce plants.